Von der Szene in die Forschung Fans als Citizen Scientists - Vomberg, Elfi Katharina (acoustic studies düsseldorf, 2023)
When fans become researchers, crossing boundaries is part of it. Citizen science makes it possible to change sides and perspectives, which can lead to productive exchanges of knowledge and experience in scholarship and society. This volume discusses the possibilities and limits of citizen science in media and cultural studies, and is the first to bring together the two disciplines of citizen science and fan research.